Foreclosure spillovers and individual well‐being: Evidence from the Great Recession. (2nd August 2021) - Makridis, Christos A.; Ohlrogge, Michael
Abstract: This paper explores the causal effect of foreclosure on individual well‐being. Using plausibly exogenous variation in the timing of interest rate changes on different types of adjustable rate mortgages, we find that a 10% rise in foreclosures is associated with a 0.58% and 0.28% decline in current and expected future life satisfaction. These effects are primarily driven by the effects on local economic optimism. The results are consistent with models of spatial externalities where large‐scale shocks generate adverse effects on communities, not just individuals.